Analysis Of Decentralization Policy Implementation In Improving The Quality Of Public Services In Rural Areas - Natsir Malawi (Pusat Riset dan Inovasi Nasional, 2024)
This study aims to analyze the implementation of decentralization policies and their impact on the quality of public services in rural areas. Decentralization has been implemented with the expectation of enhancing the efficiency and effectiveness of public services through the delegation of authority to local governments. This research employs a qualitative approach with a case study method in several villages in [Name of the Regency] Regency. Data were obtained through in-depth interviews with village government officials, community leaders, and residents, as well as through the analysis of policy documents and related reports. The results of the study indicate that the implementation of decentralization policies in rural areas has brought about several positive changes, such as increased accessibility to services and greater community participation in the decision-making process. However, there are also several challenges, including limited human and financial resources and resistance to change. These findings suggest that although decentralization has the potential to improve the quality of public services, its success is highly dependent on local capacity and sustained support from the central government. Based on these findings, the study provides strategic recommendations to strengthen the implementation of decentralization policies, including enhancing human resource capacity through continuous training, ensuring adequate budget allocation, and encouraging collaboration between central and local governments. Thus, it is hoped that the quality of public services in rural areas can continue to improve, bringing greater benefits to the local community.